Challenges implementing technology transfer as a viable pathway for equitable vaccine production and access: A case study of the mRNA vaccine hub in South Africa - Omowamiwa Kolawole; Caroline Ncube; Jeremy de Beer (Global Public Health)
In the face of the COVID-19 pandemic, there have been renewed calls for more equitable vaccine access. These calls have in turn resulted in interventions to increase vaccine manufacturing capacity as one of the key interventions to address global vaccine access. However, skill gaps in manufacturing capacity point out the critical need for technology transfer and more open science. The World Health Organization-instituted mRNA hub in South Africa has been positioned as an initiative to facilitate technology transfer for building and leveraging vaccine manufacturing capacity in low and middle income countries. Our case study examines the activities of the mRNA vaccine hub, highlighting challenges that can stifle the long-term goals of equitable vaccine production if left unaddressed. The findings suggest that for technology transfer to be effective, there must be sufficient institutional commitment, adequate funding that is fit for purpose, clear terms and an enabling legal and socio-economic environment.